Effect of the G‐protein β3 subunit 825T allele on the change of body adiposity in obese female. Issue 3 (8th November 2012) - Hwang, I. C.; Kim, K. K.; Ahn, H. Y.; Suh, H. S.; Oh, S. W.
<x xml:space="preserve">Abstract</x> No clinical studies on the lipolytic effect of guanine nucleotide‐binding protein β3 subunit gene (GNB3) 825T polymorphism have been performed. This study was a subinvestigation of a 12‐week randomized controlled trial (NCT01184560) for the additive effect of orlistat on sibutramine treatment. The analysis involved 101 obese females aged 18–49 years, genotyped at the GNB3 825 locus. To exclude any influence from potential confounders, we used an analysis of covariance model. After the intervention, fat mass proportion in total weight loss was significantly lower in subjects with a T allele than in those without a T allele (p = 0.034). GNB3 825T allele was associated with blunted fat mass reduction in obese females.